2016
DOI: 10.1103/physrevlett.116.241103
|View full text |Cite
|
Sign up to set email alerts
|

GW151226: Observation of Gravitational Waves from a 22-Solar-Mass Binary Black Hole Coalescence

Abstract: We report the observation of a gravitational-wave signal produced by the coalescence of two stellar-mass black holes. The signal, GW151226, was observed by the twin detectors of the Laser Interferometer Gravitational-Wave Observatory (LIGO) on December 26, 2015 at 03:38:53 UTC. The signal was initially identified within 70 s by an online matched-filter search targeting binary coalescences. Subsequent off-line analyses recovered GW151226 with a network signal-to-noise ratio of 13 and a significance greater than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
2,648
1
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 3,181 publications
(2,724 citation statements)
references
References 80 publications
40
2,648
1
18
Order By: Relevance
“…Since the first (and only) two direct detections of gravitational waves are associated with the merger of double black hole binaries with masses 36 − 29 M ⊙ (GW150914 [51]) and 14 − 7 M ⊙ (GW151226 [52]), before closing this chapter it is worth showing the final remnant masses expected for all the models as a function of the initial metallicity for the three initial rotation velocities (Figures 25, 26, 27). The figures show that, in the non rotating case, only low metallicity models (with [Fe/H] ≤ −1 and with initial masses in the range 50 M/M ⊙ 80) can produce black holes as massive as those associated to GW150914.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first (and only) two direct detections of gravitational waves are associated with the merger of double black hole binaries with masses 36 − 29 M ⊙ (GW150914 [51]) and 14 − 7 M ⊙ (GW151226 [52]), before closing this chapter it is worth showing the final remnant masses expected for all the models as a function of the initial metallicity for the three initial rotation velocities (Figures 25, 26, 27). The figures show that, in the non rotating case, only low metallicity models (with [Fe/H] ≤ −1 and with initial masses in the range 50 M/M ⊙ 80) can produce black holes as massive as those associated to GW150914.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Einstein-aether theory, it is also constrained by the solar system test (i.e., the constraints on α 1 and α 2 2 ), the absence of the gravitational Cherenkov radiation, and the recent GW speed bound [45], etc. Taking all the constraints into account, it was found that the speed of the one 2 The expressions for α 1 and α 2 in generalized TeVeS theory are even more complicated, so they are not presented here, either. of scalar d.o.f.…”
Section: Generalized Teves Theorymentioning
confidence: 99%
“…The gravitational wave (GW) was detected by the Laser Interferometer Gravitational-Wave Observatory (LIGO) Scientific and Virgo collaborations, which further supports General Relativity (GR) [1][2][3][4][5][6]. It is also a new tool to probe gravitational physics in the high speed, strong field regime.…”
Section: Introductionmentioning
confidence: 99%
“…If object 1(2) is a BH, set its puncture bare mass m 1(2) = M 1 (2) . If object 1(2) is a NS, construct a spherically symmetric stellar model with ADM mass M ADM 1 (2) . Compute also its rest mass M 0…”
Section: Initial Data Proceduresmentioning
confidence: 99%
“…GWs from binary black holes (BBHs) have been recently detected by the Laser Interferometer Gravitational Wave Observatory (LIGO), first detection in the transient event GW150914 [1] and second detection in the transient event GW151226 [2]. As advanced LIGO reaches designed sensitivity, GWs from double neutron star (DNS) and black hole -neutron star (BH-NS) binaries will very likely also be detected.…”
Section: Introductionmentioning
confidence: 99%